2019
DOI: 10.1002/1878-0261.12463
|View full text |Cite
|
Sign up to set email alerts
|

Perineural invasion in pancreatic cancer: proteomic analysis and in vitro modelling

Abstract: Perineural invasion ( PNI ) is a common and characteristic feature of pancreatic ductal adenocarcinoma ( PDAC ) that is associated with poor prognosis, tumor recurrence, and generation of pain. However, the molecular alterations in cancer cells and nerves within PNI have not previously been comprehensively analyzed. Here, we describe our proteomic analysis of the molecular changes underlying neuro‐epithelial interactions in PNI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 63 publications
1
28
0
1
Order By: Relevance
“…L1CAM also upregulated expression of metalloproteinase-2 (MMP-2) and MMP-9 by PDAC cells, through STAT3 activation 33 . Proteomic analysis also highlighted an increased expression of SCG2 and VGF in invaded compared to non-invaded nerves 34 . Previous research indicated that, in addition to functioning as a mitogen and a morphogen in non-neural systems, HGF can function as a guide and survival factor in the developing nervous system 7,8 .…”
Section: Discussionmentioning
confidence: 95%
“…L1CAM also upregulated expression of metalloproteinase-2 (MMP-2) and MMP-9 by PDAC cells, through STAT3 activation 33 . Proteomic analysis also highlighted an increased expression of SCG2 and VGF in invaded compared to non-invaded nerves 34 . Previous research indicated that, in addition to functioning as a mitogen and a morphogen in non-neural systems, HGF can function as a guide and survival factor in the developing nervous system 7,8 .…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, single-cell transcription data analysis showed that perineural invasion relevant module genes were associated with EMT, invasion, and metastasis (64). Moreover, the overall proteomic profiles between perineural invasion and non-perineural invasion tumor samples appeared largely similar (65). Therefore, perineural infiltration is more likely a marker for the changes in tumor microenvironment than directly correlated with genomic alterations, and we can reasonably infer that pancreatic cancer cells with perineural invasion-associated mutations and CNVs in this study might be more invasive.…”
Section: [C > G] C and More T > G Mutations At C [T > G] G But Fewer C > A Mutations At T [C > A]mentioning
confidence: 97%
“…Pancreatic ductal adenocarcinoma cells are able to induce neuronal plasticity (52). Interaction of PC with nerves is known to lead to nerve damage; described morphological changes are disrupted perineurium, distorted integrity of the whole nerve, and severely axonal edematous appearance, as a result of the invasion by pancreatic cancer cells (53).…”
Section: Pc Neurobiologymentioning
confidence: 99%